Soil organic carbon stability in forests: Distinct effects of tree species identity and traits. (30th January 2019) - Angst, Gerrit; Mueller, Kevin E.; Eissenstat, David M.; Trumbore, Susan; Freeman, Katherine H.; Hobbie, Sarah E.; Chorover, Jon; Oleksyn, Jacek; Reich, Peter B.; Mueller, Carsten W.
Abstract: Rising atmospheric CO2 concentrations have increased interest in the potential for forest ecosystems and soils to act as carbon (C) sinks. While soil organic C contents often vary with tree species identity, little is known about if, and how, tree species influence the stability of C in soil. Using a 40 year old common garden experiment with replicated plots of eleven temperate tree species, we investigated relationships between soil organic matter (SOM) stability in mineral soils and 17 ecological factors (including tree tissue chemistry, magnitude of organic matter inputs to the soil and their turnover, microbial community descriptors, and soil physicochemical properties). We measured five SOM stability indices, including heterotrophic respiration, C in aggregate occluded particulate organic matter (POM) and mineral associated SOM, and bulk SOM δ 15 N and ∆ 14 C. The stability of SOM varied substantially among tree species, and this variability was independent of the amount of organic C in soils. Thus, when considering forest soils as C sinks, the stability of C stocks must be considered in addition to their size. Further, our results suggest tree species regulate soil C stability via the composition of their tissues, especially roots. Stability of SOM appeared to be greater (as indicated by higher δ 15 N and reduced respiration) beneath species with higher concentrations of nitrogen and lower amounts of acid insoluble compounds in their roots, while SOM stability appeared to be lower (as indicated by higher respiration and lower proportions of C in aggregate occluded POM) beneath species with higher tissue calcium contents. The proportion of C in mineral associated SOM and bulk soil ∆ 14 C, though, were negligibly dependent on tree species traits, likely reflecting an insensitivity of some SOM pools to decadal scale shifts in ecological factors. Strategies aiming to increase soil C stocks may thus focus on particulate C pools, which can more easily be manipulated and are most sensitive to climate change. Abstract : We investigated effects of tree species planted in replicated plots of a common garden on five indices of soil organic matter (SOM) stability (heterotrophic soil respiration, bulk soil δ 15 N and ∆ 14 C, and C in particulate and mineral associated organic matter). Our results suggest tree species regulate SOM stability via the chemical composition of their tissues, especially roots. Some of our stability indices (C in mineral associated SOM and bulk soil ∆ 14 C), though, were negligibly dependent on tree species traits, likely reflecting an insensitivity of some SOM pools to decadal scale shifts in ecological factors. Strategies aiming to increase soil C stocks may thus focus on particulate C pools, which can more easily be manipulated and are most sensitive to climate change.